Making search work for the mobile ecosystem - Reuther, Phyllis (Henry Stewart Talks, 2009)
Has the time arrived for mobile search?, Verticalization of search, Mobile search value chain, Stakeholder expectations, The mobile search process, Mobile search market, Mobile search and federation, Federated search management
Archived at 2022/04/11